Strategy for Developing Interest of Entrepreneurship through a Culinary Business Management Course - Titin Hera Widi Handayani; Sutriyati Purwanti; Dewi Eka Murniati; Safitri Yosita Ratri (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The objectives of this study were: (1) to determine the entrepreneurial interest of Diploma students in Culinary Engineering in Culinary Business Management (CBM) course, (2) to formulate strategies for developing students’ entrepreneurial interest through the CBM course as recommendations for lectures in the next period. This ex post facto research with a descriptive approach was carried out in February to July 2019 in the Diploma Study Program of Culinary Engineering, Universitas Negeri Yogyakarta (UNY). The population of the study consisted of 40 students who took CBM in the odd semester of the 2018/2019 academic year. A purposive sampling technique was employed while the questionnaire was used in the data collection. Quantitative descriptive was used to analyze the data. The results show that: (1) Entrepreneurial interest of Diploma students of Culinary Engineering in the CBM course is 40% in the Very High category and 60% in the High category, (2) there are four strategies for developing students’ entrepreneurial interest through the CBM course, namely SO (Strength-Opportunity) strategy: while WO (Weakness-Opportunity) strategy, ST (Weakness-Opportunity) strategy, and WT (Weakness-Threat) strategy. The benefits of this study are firstly, for students, it investigates students’ entrepreneurial interests through learning CBM, for education staff, it examines the effectiveness of learning CBM in forming students’ entrepreneurial interests, and for educational institutions, it is an effort to evaluate and recommend learning CBM to form students’ entrepreneurship.